Corporate Governance dan Kualitas Auditor Melalui Fraud - Destin Alfianika Maharani; Ghonimah Zumroatun Ainiyah; Arif Nurhandika (Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to examine the effect of Corporate Governance and Auditor Quality through Fraud. The object of this study is corporate governance, audit quality and fraud using research subjects in the form of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013 - 2017. The sample selection method in this study uses purposive sampling and SPSS is used to process data on this research. The results of this study are 1) Board of Commissioners meeting frequency has a negative effect on audit quality, 2) Board of Commissioners meeting frequency has a positive effect on fraud, 3) Independent board of directors proportion has a negative effect on audit quality, 4) Independent board of directors proportion has no effect on fraud, 5) Fraud has no effect on audit quality. Keywords: corporate governance, fraud, audit quality